Analisis Efektivitas Penghapusan Sanksi Administrasi Pajak Restoran terhadap Kepatuhan Wajib Pajak Restoran pada Masa Pandemi Covid-19 di Kota Administrasi Jakarta Pusat Tahun 2021 - Budhi Yuwono; Dadang Abdul Mukti; Renisya Ayu; Salma Yasmine Putri (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Regional tax is a tax that is collected and managed by the regional removal government. And it used for funding all governmental functions and regional managing all kinds of regional income and property, one of which is Restaurant Tax. This study was conducted to find out the Effectiveness of the Restaurant Tax Administration Penalty Removal that was regulated in Governor Regulation Number 60 of 2021 in the Regional Income Board of Jakarta City to increase the compliance of restaurant taxpayers in the Covid-19 Pandemic Era. This study used a qualitative descriptive research method. Data collecting for this study was done from an interview, observation, and documentation. The result of this study indicated that the effectiveness of the restaurant tax administration penalty in increasing the compliance of taxpayers in the covid-19 pandemic era is considered effective enough if seen from the target and realization of restaurant receivables, however, it is not maximized in the implementation. The lack of maximization of the restaurant tax penalty removal in increasing the compliance of restaurant taxpayers, due to some obstacles happened such as the lack of knowledge in people about this governor regulation and the lack of taxpayer awareness.